Effect of Moringa leaf extract and set size on the bulb weight, diameter and yield of onions (Allium cepa L.) - Yaseen, Arshad; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2020)
Studying the use of natural extracts or biostimulants in improving vegetable plants is the current needs as an alternative way to the use of chemical products. This experiment was carried out to evaluate the effect of Moringa oleifera leaf extract (MLE) as a natural growth regulator on bulb diameter, weight and yield of onions ‘Texas Early White’ cultivar. Therefore, three concentrations (control, 2%, 4% and 6%) of MLE and three different onion set sizes [small (3±1 g/set), medium (6±1 g/set), and large (10±1 g/set)] were prepared in a randomized complete block design with three replications and plant spacing 20×15 cm. MLE was applied as a foliar spray directly onto the plants with the amount of 25 ml/plant every two weeks from sprouting to maturity. The achieved results indicate that the interaction of foliar spray with moringa leaf extract 4% and large set size of 10±1 g/set gave the highest value of the total yield 4802.7 g m-2, while the lowest yield 1531 g m-2 was recorded in the interaction of control and the smallest set size of 3±1 g/set. Also, a significant difference was recorded in bulb diameter separately. Thus, the largest bulb diameter 68.90 mm was obtained from the planting of the largest set size 10±1 g/set with 4% of MLE while the smallest bulb diameter 38.40 mm was recorded from the smallest set size 3 ±1 g/set with control treatment. Similarly, a significant effect was recorded in both set size and MLE separately. The highest bulb diameter 58.71 mm was achieved in the planting of the largest sets 10±1 g/set, while the lowest diameter was 42.12 mm in the planting of the smallest set size 3 ±1 g/set. Similar results were recorded for the bulb weight and total yield. The concentration of 4% MLE produced the highest bulb weight 99.74 g/bulb and yield 3324.5 g m-2, while the lowest bulb weight and yield was obtained in the control treatment 55.61 g/bulb, and 1869.3 g m-2. Consequently, the results indicate the positive effect of Moringa leaf extract which can be applied as a natural substance in the form of foliar spray at critical growth stages to improve the growth and yield of dry onions.